Building valve amplifiers - Jones, Morgan (Newnes, 2013)
Building Valve Amplifiers is a unique hands-on guide for anyone working with tube audio equipment--as an electronics hobbyist, audiophile or audio engineer. This 2nd Edition builds on the success of the first with technology and technique revisions throughout and, significantly, a major new self-build project, worked through step-by-step, which puts into practice the principles and techniques introduced throughout the book. Particular attention has been paid to answering questions commonly asked by newcomers to the world of the valve, whether audio enthusiasts tackling their first build or more experienced amplifier designers seeking to learn about the design principles and trade-offs of "glass audio." Safety considerations are always to the fore, and the practical side of this book is reinforced by numerous clear illustrations throughout. The only hands-on approach to building valve and tube amps--classic and modern--with a minimum of theory. Design, construction, fault-finding, and testing are all illustrated by step-by-step examples, enabling readers to clearly understand the content and succeed in their own projects. Includes a complete self-build amplifier project, putting into practice the key techniques introduced throughout the book